2015
DOI: 10.1016/j.ijgo.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of single-port versus conventional laparoscopic hysterectomy

Abstract: There is no significant difference in the frequency of perioperative complications between SPLH and CLH. However, the higher rate of procedure failure in SPLH should be taken into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
4
20
0
Order By: Relevance
“…In this randomized trial, we evaluated safety and effectiveness of LESS hysterectomy compared to the conventional laparoscopic hysterectomy. Our findings confirm the findings from three meta-analyses, defining LESS hysterectomy as a safe surgical procedure [6,8]. The primary aim of the trial was to evaluate the blood loss during surgery.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In this randomized trial, we evaluated safety and effectiveness of LESS hysterectomy compared to the conventional laparoscopic hysterectomy. Our findings confirm the findings from three meta-analyses, defining LESS hysterectomy as a safe surgical procedure [6,8]. The primary aim of the trial was to evaluate the blood loss during surgery.…”
Section: Discussionsupporting
confidence: 86%
“…All participating surgeons were certified as MIC-II-III by the German Study Group for Gynaecologic Endoscopy (Arbeitsgemeinschaft Gynäkologische Endoskopie: AGE). Additionally, we demonstrated that the operative time was comparable in both groups which has been confirmed in recent trials [6,8,17,18]. Patients within the LESS group experienced significantly less pain 24 h postoperatively (p = 0.006), while pain scores were comparable at days 3, 5, 7, and 2 months postoperatively.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…YH Park was the first person who reported that he use a homemade single port device to perform laparoendoscopic single-site nephrectomy [11]. Several meta-analysis researches have been published on the safety and efficacy of LESS in recent years [9,[12][13][14]. However, it has been unclear whether LESS offers benefits over multiport LH.…”
Section: Discussionmentioning
confidence: 99%